American woman today, free or frustrated? - Gould, Elsie M. 1930-. (Englewood Cliffs, N.J. Prentice-Hall, 1977)
Discusses the position of women throughout history and the events that have brought about a change in their status and experiences.
Bibliography: p. 116-120.
Keywords: Women -- United States; Women's rights -- United States; Feminism -- United States; Women's rights; Feminism